Solved Exercises in Fractional Calculus - Capelas de Oliveira, Edmundo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book contains a brief historical introduction and state of the art in fractional calculus. The author introduces some of the so-called special functions, in particular, those which will be directly involved in calculations. The concepts of fractional integral and fractional derivative are also presented. Each chapter, except for the first one, contains a list of exercises containing suggestions for solving them and at last the resolution itself. At the end of those chapters there is a list of complementary exercises. The last chapter presents several applications of fractional calculus.
A bit of history -- Special functions -- Mittag-Leffler Functions -- Integral transforms -- Fractional derivatives -- Applications and add-ons.
Keywords: Engineering mathematics; Engineering -- Data processing; Mathematical analysis; Mathematical and Computational Engineering Applications; Integral Transforms and Operational Calculus